Bis(azulene) "submarine" metal dimer sandwich compounds (C10H8)2M2 (M = Ti, V, Cr, Mn, Fe, Co, Ni): Parallel and opposed orientations. Issue 2 (27th July 2015) - Wang, Hongyan; Wang, Hui; King, R. Bruce; Schaefer, Henry F.
Abstract : The opposed and parallel structures for the binuclear bis(azulene) "submarine" sandwiches (C10 H8 )2 M2 (M = Ti, V, Cr, Mn, Fe, Co, Ni) have been optimized using density functional theory. The lowest energy (C10 H8 )2 M2 structures of the early transition metals Ti, V, Cr, and Mn have the azulene units functioning as bis(pentahapto) ligands to each metal atom similar to the azulene ligand in the long‐known molybdenum carbonyl complex (η 5, η 5 ‐C10 H8 )Mo2 (CO)6 . The metal–metal bonds in these early transition metal structures have distances and Wiberg bond indices consistent with the formal bond orders required to give each metal atom an 18‐electron configuration for the singlet structures and a 17‐electron configuration for the triplet structures. For the later transition metals Fe, Co, and Ni, the lowest energy (C10 H8 )2 M2 structures contain pentahapto‐trihapto azulene ligands with an uncomplexed CC double bond, similar to that in the long‐known iron carbonyl complex (η 5, η 3 ‐C10 H8 )Fe2 (CO)5 . The parallel (η 5, η 3 ‐C10 H8 )2 M2 (M = Fe, Co, Ni) structures contain metallocene subunits with their metal atoms at long nonbonding distances of 3.5–3.9 Å from the other metal atom, which is located between the azulene C7 rings. Higher energy opposed (C10 H8 )2 Fe2 structures contain an unprecedented distorted η 6, η 4 ‐azulene ligand using six carbon atoms for bonding to one iron atom as a hexahapto fulvene ligand and the remaining four carbon atoms for bonding to the other iron atom as a tetrahapto diene ligand. © 2015 Wiley Periodicals, Inc. Abstract : The lowest energy (C10 H8 )2 M2 submarine sandwich structures of the early transition metals Ti, V, Cr, and Mn have the azulene units functioning as bis(pentahapto) ligands to each metal atom. For the later transition metals Fe, Co, and Ni the lowest energy (C10 H8 )2 M2 structures contain pentahapto‐trihapto azulene ligands with an uncomplexed CC double bond